2022
DOI: 10.1017/ice.2022.211
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-onset bacteremia and fungemia: An evaluation of predictors and feasibility of benchmarking comparing two risk-adjusted models among 267 hospitals

Abstract: Objectives: To evaluate the prevalence of hospital-onset bacteremia and fungemia (HOB), identify hospital-level predictors, and to evaluate the feasibility of an HOB metric. Methods: We analyzed 9,202,650 admissions from 267 hospitals during 2015–2020. An HOB event was defined as the first positive blood-culture pathogen on day 3 of admission or later. We used the generalized linear model method via negative binomial regression to identify variables and risk markers for HOB. Standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In this multicenter database encompassing almost 800,000 hospitalized adult patients, there were ∼4 times as many non-CLABSI HOB cases as CLABSI cases (1,574 vs 403) using a conservative EHR-based case definition that only included the first positive blood culture with a CDC-designated BSI pathogen. 8 Compared with matched controls, both CLABSIs and non-CLABSI HOB cases were associated with increases in LOS and significantly higher hospital costs, mortality rates, and 30-day readmission rates. Rock et al 4 reported that among ICU patients, changes in HOB rates are highly associated with changes in CLABSI rates.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this multicenter database encompassing almost 800,000 hospitalized adult patients, there were ∼4 times as many non-CLABSI HOB cases as CLABSI cases (1,574 vs 403) using a conservative EHR-based case definition that only included the first positive blood culture with a CDC-designated BSI pathogen. 8 Compared with matched controls, both CLABSIs and non-CLABSI HOB cases were associated with increases in LOS and significantly higher hospital costs, mortality rates, and 30-day readmission rates. Rock et al 4 reported that among ICU patients, changes in HOB rates are highly associated with changes in CLABSI rates.…”
Section: Discussionmentioning
confidence: 93%
“…CoNS were excluded from eligible pathogens for non-CLABSI HOB. 8 For patients who had positive urine cultures with the same microorganism as the HOB, Enterobacteriaceae was the most common microorganism (61% of positive urine cultures in all HOB admissions). S. aureus was the most common shared microorganism present in respiratory (42%) and skin/soft tissue (53%) cultures (Supplementary Table S5).…”
Section: Association Of Clabsi and Non-clabsi Hob With Sites Of Infec...mentioning
confidence: 95%
See 2 more Smart Citations
“…[1][2][3][4] Central line-associated bloodstream infections (CLABSIs) are a mandated quality metric, but bloodstream infections from other sources also result in significant morbidity and cost. 1,5 Hospital-onset bacteremia and fungemia (HOB) has been suggested as a more comprehensive quality metric, [6][7][8][9] and at the time of this writing, has currently passed the National Quality Forum (NQF) Patient Safety Committee review as a recommended metric to the Centers for Medicare & Medicaid Services (CMS). 10 Peripheral intravenous (IV) devices are documented sources of bacteremia.…”
Section: Introductionmentioning
confidence: 99%